Influence of microwave disinfection on the linear dimensional stability of complete dentures: A clinical study - Frederico Manzolli Basso, Michael [UNESP]; Giampaolo, Eunice Teresinha [UNESP]; Vergani, Carlos Eduardo [UNESP]; Machado, Ana Lúcia [UNESP]; Pavarina, Ana Cláudia [UNESP]; Compagnoni, Marco Antonio [UNESP] (My University, 2010)
This clinical study evaluated the effect of two microwave disinfection protocols at 650 W for 3 minutes (group 1, once a week; group 2, three times a week) on the linear dimensional stability of complete dentures. Measurements were taken across four reference points: before the first microwave disinfection (baseline) and after each week of disinfection. Furthermore, the dentures were monitored clinically. Group 2 showed significantly greater shrinkage than group 1 in all evaluated weeks. During clinical monitoring, no significant findings were observed. Even though dimensional changes occurred, the clinical evaluation did not yield any changes in either group. © 2010 by Quintessence Publishing Co Inc.